A Case With 4 de Novo Copy Number Variations With Clinical Features That Overlap 1q43q44 Microdeletion and 3q29 Microduplication Syndromes. (21st September 2018) - Kessi, Miriam; Peng, Jing; Yang, Lifen; Duan, Haolin; Tang, Yulin; Yin, Fei
1q43q44 microdeletion syndrome is characterized by intellectual disability/global developmental delay, epilepsy, dysmorphic facies, stereotypic movement, language delay, recurrent infections, dental anomalies, and hand and foot anomalies. Microcephaly and corpus callosum dysplasia are present in some cases depending on gene content. 3q29 microduplication syndrome is characterized by intellectual disability, language delay, microcephaly, and dental anomalies. We report the first case with 4 de novo copy number variations with clinical features which overlap 1q43q44 microdeletion and 3q29 microduplication syndromes. Our case presented with global developmental delay, epilepsy, recurrent infections, stereotypic movements, speech delay, microcephaly, facial dysmorphism, bilateral clinodactyly, and small puffy feet with metatarsus varus; however, she had no corpus callosum dysplasia. Our case highlights the role of multiple copy number variations in the occurrence of a certain phenotype. Moreover, it supports the theory that the loss of HNRNPU gene function cannot explain the occurrence of microcephaly and abnormalities of the corpus callosum in 1q43q44 microdeletion syndrome.